Incidence of and survival after surgery for metastatic spine disease: a nationwide register-based study between 1997 and 2020 from Finland - Toivonen, Leevi A; Ponkilainen, Ville; Repo, Jussi P; Mattila, Ville M (Acta orthopaedica, 2025)
Background and purpose: Information on metastatic spine disease (MSD) based on nationwide data on trends and postoperative survival is limited but is needed to optimize treatment in this population. We aimed to assess the incidence of and survival rates after MSD surgery.Methods: This retrospective nationwide register-based study combined data from the Finnish Cancer Registry, Finnish Care Register for Health Care, and the Finnish Cause of Death Register from 1997 to 2020. Surgeries were identified using diagnosis and procedural codes, with primary spine pathologies excluded. Incidence rates were calculated per 100,000 inhabitants and adjusted for age and sex. Survival analysis was conducted using the Kaplan–Meier estimator.Results: 1,845 patients underwent 1,992 surgeries, with a mean age of 65 years; 58% were men. The most common primary cancers were prostate cancer (15.1%), breast cancer (11.6%), and myeloma (10.6%). The incidence of MSD surgery increased by 87%, from 1.05 to 1.97 per 100,000 person-years. Surgery increased most among patients aged 70–79 years. Over the same period, the 6-month survival remained fairly stable. The overall survival probabilities were 57% (95% confidence interval [CI] 54–59) at 1 year, 44% (CI 42–46) at 2 years, 28% (CI 26–30) at 5 years, and 18% (CI 16–20) at 10 years. The 1-year survival was highest in patients with breast cancer at 75% (CI 69–81) and lowest in patients with kidney cancer at 45% (CI 38–53) and prostate cancer at 47% (CI 42–53).Conclusion: Finnish nationwide data showed an increase in MSD surgery between 1997 and 2020 with a stable postoperative survival of 57% (CI 48–69) to 76% (CI 66–89) at 6 months.